2021
DOI: 10.1097/pgp.0000000000000764
|View full text |Cite
|
Sign up to set email alerts
|

International Endocervical Adenocarcinoma Criteria and Classification (IECC): An Independent Cohort With Clinical and Molecular Findings

Abstract: and Classification (IECC) has reorganized the classification of endocervical adenocarcinomas (ECAs), separating them into human papilloma virus (HPV)-associated (HPVA) and HPVA independent (HPVI) categories. In this study, we sought to revalidate the IECC clinical findings in an independent cohort and assess the mutational differences between HPVA and HPVI ECAs using next generation sequencing. Consecutive cases of ECAs were reclassified under the IECC. Clinicopathologic information was collected and tissue wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 36 publications
1
23
0
1
Order By: Relevance
“…A recent investigation on a small cohort of EACs reconfirmed that HPVA had better survival than HPVI. 13 In addition, our study indicated that mutant-type p53 expression was substantially higher in HPVI than in HPVA, and was a significant indicator for poor survival in EAC. A prospective cohort study showed that p53 over expression was an adverse biomarker for patient survival in cervical carcinomas including EAC.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…A recent investigation on a small cohort of EACs reconfirmed that HPVA had better survival than HPVI. 13 In addition, our study indicated that mutant-type p53 expression was substantially higher in HPVI than in HPVA, and was a significant indicator for poor survival in EAC. A prospective cohort study showed that p53 over expression was an adverse biomarker for patient survival in cervical carcinomas including EAC.…”
Section: Discussionmentioning
confidence: 58%
“…The IECC (the prototype of WHO classification, 2020) not only had superior diagnostic reproducibility among gynecological pathologists compared to the fourth WHO classification (2014), but also showed excellent prediction of HPV status. 4,12,13 More importantly, emerging evidence has demonstrated the relevance of the classification with the clinical outcomes. [13][14][15] In this retrospective study, we independently validated the clinicopathological and pathogenic significance of the novel WHO classification in a large cohort of EAC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After diagnosis in two large pathological centers, the patient was considered to have HPVA, and the positive immunohistochemical P16 and HPV E6 and E7 mRNA were also consistent with this diagnosis. The prognosis of HPVA is better than that of non-HPV cervical adenocarcinoma ( 8 ). There is no standard FIGO staging method for cervical adenocarcinoma of large cysts.…”
Section: Discussionmentioning
confidence: 99%